Community-development programs and the implications for women migrant workers’ pre-departure preparation in eastern Indonesia - Metboki, Yakob; Ledo, Jolly Petrecia Hosang (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2019)
This paper aims to describe the implementation of the community development programs and the benefits originated from the prospective women migrant workers’ responses after taking the training. The problems are "What are community development programs for prospective women migrant workers during pre-departure preparation? and, “What are the benefits originated from participants' responses on implemented programs?  The present study applies descriptive qualitative method, where data collection techniques utilized needs analysis and surveys. Data analysis comprises data collection, data presentation, data interpretation and conclusions. Total participants are 41 prospective maids. The results reveal that the implementation of community development programs has significant implications for prospective women migrant workers’ pre-departure preparation before leaving for the receiving countries. Having participated in the programs, the participants disclose the benefits they gain from each acting program. First, Basic English teaching benefited them to use English according to work needs. Second, the character-building program has nurtured them with life skills and self-understanding of the importance of being whole persons to provide good services. Last, they do not simply experience training but also complete concrete tasks through work skills training. Overall, the implementation of the community development programs in this study promotes significant impact to prospective Indonesian women migrant maids’ pre-departure preparation.